2021
DOI: 10.1007/s13770-021-00352-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of MSC-Derived Exosomes Depending on Cell Culture Media for Regenerative Bioactivity

Abstract: BACKGROUND: In order to produce and isolate the exosome derived from the cell of interests, a serum free environment (starvation) has been essential for excluding the unknown effect from serum-derived exosomes. Recently, serum-free culture media have been developed as a substitute for serum supplemented media so that MSC proliferates with maintaining the original characteristics of the cells in a serum free condition. Due to the different properties of the exosomes representing the states and characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…An investigation into different administration routes to determine the optimal delivery method and frequency of administration would help maximize benefits. The last important limitation is the presence of residual proteins and EVs from FCS in the studied CM, which could potentially distort and even reduce the therapeutic efficacy of the MMSC secretome [ 44 ]. However, we used identical cell culture conditions, so we assume that the contribution of FCS-derived EVs was the same for all cell cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation into different administration routes to determine the optimal delivery method and frequency of administration would help maximize benefits. The last important limitation is the presence of residual proteins and EVs from FCS in the studied CM, which could potentially distort and even reduce the therapeutic efficacy of the MMSC secretome [ 44 ]. However, we used identical cell culture conditions, so we assume that the contribution of FCS-derived EVs was the same for all cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent studies showing that the regenerative potential of EVs from fetal serum is significantly lower than vesicles from MMSCs [ 45 ]. Interestingly, EVs collected from the MMSC cultured in fetal serum–containing medium had greater wound healing and angiogenic effects for endothelial cells compared with FBS-derived EVs [ 44 ]. Based on the literature, the MMSC secretome examination may benefit from the use of chemically defined, serum-free, and xeno-free medium that is not only optimized for cell growth and viability for a variety of cell types, but is also free of exogenous contaminating fetal serum-derived EVs and extracellular protein/RNA species [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and purification of these vesicles is not uniform across different studies, and, thus, advantages seen using a single isolation method might not be present in other populations of MSC-derived exosomes [ 130 ]. One study showed that varying the conditions under which exosomes are isolated led to a significant difference in the expression of pro-inflammatory cytokines within the different exosome populations [ 131 ]. Exosomes’ ability to modulate inflammation should be further explored in the context of LSCD; however, investigators should rigorously adhere to standardized isolation techniques to derive a homogenous population of vesicles.…”
Section: Therapeutic Regeneration Of the Limbal Nichementioning
confidence: 99%
“…Recent studies have demonstrated that transplanted stem cells can differentiate into neuronal cells and glial cells and that substantial functional recovery is mostly due to paracrine signaling effects provided by grafted stem cells [7][8][9]. However, several safety issues, including immunogenic risk, still remain [10].…”
Section: Introductionmentioning
confidence: 99%
“…EVs exhibit tetraspanins CD63, CD81, and CD9 on the surface and present the endo-lysosomal regulatory transport protein (ALIX) [11,12]. MSC-derived EVs have been regarded to have a similar therapeutic potency as MSCs without the potential safety risks [10]. For the regeneration of neurological disorders, EV-based therapy is also promising as it is a neuroprotective paracrine cargo containing abundant proteins and microRNAs [13].…”
Section: Introductionmentioning
confidence: 99%